TEMPORAL AND DEPTH VARIATION OF SEISMIC PARAMETERS PRIOR TO MAJOR EARTHQUAKES IN PALU REGION, INDONESIA - Rahmalia, Diah Ayu; Andinisari, Ratri; Tampubolon, Danastri Lintang Pitaloka; Aminuddin, Jamrud; Yuliardi, Amir Yarkhasy; Fadhilah, Firda Haifa (JGE (Jurnal Geofisika Eksplorasi), 2025)
The Palu region in Central Sulawesi is high tectonic activity area due to a subduction zone and major fault system, which resulted in high seismic intensity. The b value, as the seismic characteristic, is a valuable parameter for evaluating stress conditions and earthquake precursors. This study aimed to investigate the temporal and depth variations of the b-value in the Palu region. We observed earthquake distribution over 75 years from 1950 to 2025, which was obtained from the United States Geological Survey catalog. We applied the declustering analysis to isolate the mainshock events by using the space-time window method. We also conducted the magnitude completeness estimation and b-value calculation with ZMAP. This result showed that the average b-value was around 0.88, which was indicated as an intermediate level of seismic activity, influenced by subduction and the Palu-Koro Fault. Decreasing b-value was observed prior to the 1996 and 2018 earthquakes, followed by an increase in the parameter. This pattern exhibited stress accumulation and release, which was represented by the magnitude distribution. This lowering characteristic of b-value could be a long term precursor to major earthquakes. Furthermore, the depth variation of b-value revealed high values in the upper crust (0–10 km), a decrease around 20–30 km, and a secondary increase near 40 km, which corresponds to the Moho, as indicated by shear wave velocity profiles. These results provide insight into the crustal structure and seismic behavior in a tectonically complex and tsunami-prone region.